2021
DOI: 10.1007/s12022-021-09674-1
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Papillary Thyroid Carcinoma to Anaplastic Carcinoma in Metastatic Lymph Nodes: Solid/Insular Growth and Hobnail Cell Change in Lymph Nodes Are Predictors of Subsequent Anaplastic Transformation

Abstract: Most anaplastic thyroid carcinomas (ATCs) arise from papillary thyroid carcinoma (PTC). This process is also called anaplastic transformation, and the morphological harbingers of this phenomenon in nodal recurrence have not been assessed systematically. For this reason, the current study focused on features of 10 PTCs with regional lymph node recurrence that was accompanied with disease progression due to anaplastic transformation in at least one of the nodal recurrences. The findings of additional 19 PTCs whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…This variant is distinguished histologically and cytologically by three distinct architectural and cytologic features: micro-papillae lacking true fibrovascular cores, cells with eosinophilic cytoplasm and apically placed nuclei with a decreased nucleus/cytoplasm ratio (hobnail appearance), and loss of cellular cohesion that form characteristic hobnail cells in at least 30% of the neoplastic cells [17] , [31] . In recurrent PTCs, an increased mitotic count, the appearance of necrosis, high grade features, might be predictors of a subsequent anaplastic transition [32] . Most typical PTCs do not display solid and insular development, the appearance of these components in recurrent PTCs might indicate an anaplastic transition [32] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variant is distinguished histologically and cytologically by three distinct architectural and cytologic features: micro-papillae lacking true fibrovascular cores, cells with eosinophilic cytoplasm and apically placed nuclei with a decreased nucleus/cytoplasm ratio (hobnail appearance), and loss of cellular cohesion that form characteristic hobnail cells in at least 30% of the neoplastic cells [17] , [31] . In recurrent PTCs, an increased mitotic count, the appearance of necrosis, high grade features, might be predictors of a subsequent anaplastic transition [32] . Most typical PTCs do not display solid and insular development, the appearance of these components in recurrent PTCs might indicate an anaplastic transition [32] .…”
Section: Discussionmentioning
confidence: 99%
“…In recurrent PTCs, an increased mitotic count, the appearance of necrosis, high grade features, might be predictors of a subsequent anaplastic transition [32] . Most typical PTCs do not display solid and insular development, the appearance of these components in recurrent PTCs might indicate an anaplastic transition [32] . Amacher et al reported when hobnail pattern is observed in PTC, it is strongly associated with other histologic variants known to be more clinically aggressive [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Among these, four had also focal dedifferentiation characterized by a focal tumor component (less than 30% of the tumor volume) with solid growth, increased mitotic activity and/or necrosis. Focal dedifferentiation has been shown to alter the prognosis of patients with PTCs in former series ( 28 , 29 ). However, the current series also underscored that this finding also correlates with adverse biology.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Odate et al published 10 cases of PTC operated on at Ito Hospital and Yamanashi University for 40 years [67]. In these 10 cases, the tumor recurred in the lymph nodes, developed anaplastic transformation, and eight patients died of tumor [67]. The Ki-67 labeling index was low at <5% in 8 cases of primary thyroid PTC, and it was not available in the other 2.…”
Section: Message To Endocrinologists and Thyroid Surgeonsmentioning
confidence: 99%